Risk of total knee replacement after proximal tibia fracture: a register-based study of 7,701 patients - Tapper, Valtteri S; Pamilo, Konsta J; Haapakoski, Jaason J; Toom, Alar; Paloneva, Juha (Acta Orthopaedica, 2022)
Background and purpose — Post-traumatic knee osteoarthritis following proximal tibia fracture (PTF) is a common complication that may lead to total knee replacement as secondary treatment (TKRS). We determined the risk of TKRS following PTF, whether treated nonoperatively or operatively, and compared the results with a 38-fold control group without prior PTF. Patients and methods — We identified all patients over 18 years of age in Finland with PTF treated during the period 2009–2018 from the Finnish Hospital Discharge Register (FHDR) and Finnish Arthroplasty Register (FAR). Age, sex, treatment method, follow-up time, and possible TKRS were recorded. Results — 7,701 patients were treated for PTF during the period 2009–2018. Over the 5.1-year (SD 3.1) follow-up, TKRS was performed in 340 (4.3%) patients with a prior PTF after a mean of 2.1 (SD 2.0) years post-fracture. TKRS was needed in 138 (3.7%, HR 1.8) patients in the nonoperatively treated group and in 202 (5.0%, HR 3.2) patients in the operatively treated group. Operative treatment, female sex, and high age were identified as risk factors for TKRS. The incidence of TKRS was highest during the first 2 years after fracture and remained elevated throughout the follow-up. Interpretation — Patients with a prior PTF had a 1.8- to 3.2-fold higher risk of TKRS compared with controls during the first 5 years post-fracture. Risk of TKRS was associated with an operatively treated PTF, female sex, and high age. The patients in the operative group likely sustained more complex fractures, while female sex and age may be explained by more osteoporotic bone quality.